COMMUNICATION STRATGEIES USED BY BILINGUAL CHILDREN OF INTERRACIAL MARRIAGE FAMILY (A CASE STUDY) - Erawan, P. S. B.; Padmadewi, N. N.; Saputra, I. N. P. H. (Universitas Pendidikan Ganesha, 2018)
Abstract This study aimed at describing the communication strategies used by bilingual children of interracial marriage family in doing interaction with their family at Singapadu village, Sukawati distric, Gianyar regency, Bali province. The subjects of this study were two bilingual children of interracial marriage family. The investigation focused on the types of communication strategies that they used in doing interaction with their family, the most frequently communication strategy that they applied when they were doing the interaction, and their reasons in using the communication strategies. This research was a case study which combined qualitative and quantitative analysis in which a triangulation technique was used. The results of the data analysis show that the bilingual children used seven communication strategies which included: topic avoidance, approximation, circumlocution, clarification request, paralanguage, using pictures or objects to help conveying message, and speaking slowly. The most frequently used communication strategy used by the bilingual children was paralanguage. There were three main reasons that they stated in using the strategies, the first to make the family understand of what they expected, the second because the strategies were easy and natural, and the last reason because the strategies were quick to be used. Keywords: Communication strategies, children of interracial marriage family